Web-Based Project Assessment - Supianto; Kumaidi; Khaerudin (International Journal of Psychosocial Rehabilitation, 2020)
This research is a library research that seeks to examine the literature relating to research problems by selecting, reading, and studying research relevant to the title of this research. Data was collected through literature surveys related to web-based assessment and project-based assessment. Data analysis was conducted by editing, classification, and interpretation. The purpose of this study is to examine a variety of previous studies that have discussed web-based assessment, strengths, and weaknesses. This study also seeks to review studies on project-based learning and assessment. The researcher briefly describes the definition of web-based assessment, then maps the advantages of web-based assessment. The results of this study indicate that basically, web-based assessment refers to assessment models such as e-test, e-assessment, computer-based test, and internet-based test. The advantages of web-based assessment are that it is more flexible, decreases paper consumption, data collection, and data analysis is fast, provides timely feedback, eases teacher assignments, and facilitates e-learning. However, there are several obstacles, including the visual design of the web interface that might be a problem for users. Ineffective menu layout and poor navigation cause users to waste too much of their time. It is also necessary to ensure that students can use the online learning system effectively. In practice, web-based project appraisal can adapt existing assessment methods, such as peer assessment, self-assessment, and group assessment. These methods can be alternative assessments that educators can choose to assess student projects on the web.